Overuse injuries and burnout in youth sports: a position statement from the American Medical Society for Sports Medicine - DiFiori, J. P.; Benjamin, H. J.; Brenner, J.; Gregory, A.; Jayanthi, N.; Landry, G. L.; Luke, A. (Clinical Journal of Sport Medicine, 2014)
BACKGROUND • Youth sport participation offers many benefits including the development of self-esteem, peer socialization, and general fitness. • However, an emphasis on competitive success, often driven by goals of elite-level travel team selection, collegiate scholarships, Olympic and National team membership, and even professional contracts, has seemingly become widespread. • This has resulted in increased pressure to begin high-intensity training at young ages. • Such an excessive focus on early intensive training and competition at young ages rather than skill development can lead to overuse injury and burnout. PURPOSE • To provide a systematic, evidenced-based review that will: ° Assist clinicians in recognizing young athletes at risk for overuse injuries and burnout. ° Delineate the risk factors and injuries that are unique to the skeletally immature young athlete. ° Describe specific high-risk overuse injuries that present management challenges and/or can lead to long-term health consequences. ° Summarize the risk factors and symptoms associated with burnout in young athletes. ° Provide recommendations on overuse injury prevention. SUMMARY AND RECOMMENDATIONS Overuse injuries are common in children and adolescents participating in sports, particularly for those participating on a nearly continuous yearly schedule. In young athletes these injuries are the result of a complex interaction of multiple factors, including growth-related factors that are unique to this population. Although often thought to be selflimited injuries, recovery time can be lengthy, often more so than acute injuries. In addition, some overuse injuries have the potential to negatively affect future participation, and may result in long-term health consequences. Further, in the setting of competitive youth sports, the specter of burnout is also a concern. It is thus essential that health care providers provide comprehensive evaluation and treatment of young athletes with overuse injuries and/or those who exhibit features of burnout. In addition to the recommendations regarding prevention, the following summary statements are made: 1. Overuse injuries are underreported in the current literature because most injury definitions have focused on time loss from sport. 2. Preparticipation exams may identify prior injury patterns and provide an opportunity to assess sport readiness. 3. A history of prior injury is an established risk factor for overuse injuries and should be noted as part of each injury assessment. 4. Adolescent female athletes should be assessed for menstrual dysfunction as a potential predisposing factor to overuse injury. 5. Parents and coaches should be educated regarding the concept of sport readiness. Variations in cognitive development, as well as motor skills, should be considered when setting goals and expectations. 6. Early sport specialization may not lead to long-term success in sports and may increase risk for overuse injury and burnout. With the exception of early entry sports such as gymnastics, figure skating, and swimming/diving, sport diversification should be encouraged at younger ages. 7. When an overuse injury is diagnosed, it is essential to address the underlying cause(s). The athlete, parents, and coaches should be involved in reviewing all risk factors and developing a strategy to attempt to avoid recurrent injury. 8. All overuse injuries are not inherently benign. Clinicians should be familiar with specific high-risk injuries, including stress fractures of the femoral neck, tarsal navicular, anterior tibial cortex and physis, and effort thrombosis.